One Year of Continuous Positive Airway Pressure Adherence Improves Cognition in Older Adults With Mild Apnea and Mild Cognitive Impairment. Issue 2 (March 2020) - Wang, Yanyan; Cheng, Cynthia; Moelter, Stephen; Fuentecilla, Jamie L.; Kincheloe, Kelly; Lozano, Alicia J.; Carter, Patricia; Gooneratne, Nalaka; Richards, Kathy C.
Abstract : Background: Mild cognitive impairment frequently represents a predementia stage of Alzheimer's disease. Although obstructive sleep apnea is increasingly recognized as a common comorbidity of mild cognitive impairment, most apnea research has focused on middle-aged adults with moderate-to-severe obstructive sleep apnea. Mild obstructive sleep apnea, defined as 5–14 apneas or hypopneas per hour slept, is common in older adults. Little is known about the effect on cognition of adherence to continuous positive airway pressure (CPAP) treatment of obstructive sleep apnea in older adults with mild obstructive sleep apnea and mild cognitive impairment. Objective: The objective of this study was to explore the effect of CPAP adherence on cognition in older adults with mild obstructive sleep apnea and mild cognitive impairment. Methods: We conducted a secondary analysis of data from Memories 1, a 1-year quasiexperimental clinical trial on the effect of CPAP adherence in older adults with mild cognitive impairment and obstructive sleep apnea. Those with mild obstructive sleep apnea were divided into two groups based on their CPAP adherence over 1 year: (a) CPAP adherent group (mild cognitive impairment + CPAP) with an average CPAP use of ≥4 hours per night and (b) CPAP nonadherent group (mild cognitive impairment − CPAP) with an average CPAP use of <4 hours per night. Individuals currently using CPAP were not eligible. A CPAP adherence intervention was provided for all participants, and an attention control intervention was provided for participants who chose to discontinue CPAP use during the 1-year follow-up. Descriptive baseline analyses, paired t tests for within-group changes, and general linear and logistic regression models for between-group changes were conducted. Results: Those in the mild cognitive impairment + CPAP group compared to the mild cognitive impairment – CPAP group demonstrated a significant improvement in psychomotor/cognitive processing speed, measured by the Digit Symbol Coding Test. Eight participants improved on the Clinical Dementia Rating Scale, whereas six worsened or were unchanged. Twelve participants rated themselves as improved on the Alzheimer's Disease Cooperative Study–Clinical Global Impression of Change Scale, whereas three reported their status as worsened or unchanged. The mild cognitive impairment + CPAP group had greater than an eightfold increased odds of improving on the Clinical Dementia Rating and greater than a ninefold increased odds of improving on the Alzheimer's Disease Cooperative Study–Clinical Global Impression of Change Scale, compared to the mild cognitive impairment − CPAP group. Discussion: CPAP adherence may be a promising intervention for slowing cognitive decline in older adults with mild obstructive sleep apnea and mild cognitive impairment. A larger, adequately powered study is needed.